Exosomes expressing neuronal autoantigens induced immune response in antibody-positive autoimmune encephalitis. (March 2021) - Gu, Jiachen; Jin, Tao; Li, Zongshan; Chen, Huimin; Xia, Hongbo; Xu, Xiaomin; Gui, Yaxing
Highlights: CSF or sera derived exosomes from AE contained specific neuronal autoAgs in protein aggregates. Control subjects had no detectable levels of these neuronal autoAgs. Antibodies against neuronal autoAgs were developed after immunization with exosomes isolated from AE patients. Increased frequency of neuronal autoAgs-specific IL-17 and IFN-γ in splenocytes from AE derived exosomes immunized mice. Abstract: The immunological role of exosomes in autoimmune encephalitis (AE) remains uncharacterized and not examined. In this study we ought to determine whether exosomes are generated in AE and to define the presence of cell surface neuronal autoantigens (autoAgs) in the cargo. Exosomes were isolated from cerebrospinal fluid (CSF) from 12 patients with anti -N- methyl-d -aspartate (NMDA) receptor encephalitis, 8 patients with anti-gamma-aminobutyric acid-B (GABAB ) receptor encephalitis, 8 patients with anti-leucine-rich glioma-inactivated 1 (LGI1) encephalitis, 8 patients with anti-contactin-associated protein-like 2 (CASPR2) encephalitis, 10 patients with anti-α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid 1, 2 (AMPA) receptor encephalitis and 30 control individuals negative of antibodies against neuronal autoAgs. Western blot demonstrated that CSF or sera derived exosomes from AE contained specific neuronal autoAgs in protein aggregates, however, control subjects had no detectable levels of these neuronal autoAgs. In addition, development of antibodies against NMDAR, GABAB R, LGI1, CASPR2, and AMPAR were detected in the sera after 30 days immunization of C57BL/6 J mice with exosomes isolated from antibody positive AE patients; Enzyme-linked immunospot (ELISpot) assay demonstrated increased frequency of neuronal autoAgs-specific IL-17 and IFN-γ in splenocytes from AE derived exosomes immunized mice. We concluded that exosomes expressing neuronal autoAgs were present in CSF from antibody positive AE patients, and we propose these exosomes carrying neuronal autoAgs would play an important role in the immune pathogenesis of autoimmune encephalitis.